Translational Spaces: Virtual narratives of being and belonging. Issue 2 (1st December 2017) - Tavera, Santiago
The concept of translation implies a dynamic motion of subjects and objects to perceive, remember and experience physical and digital elements across geographical, linguistic, physical, psychological and virtual borders. Translational Spaces is a project that consists of a series of 2D and 3D animations combined with written fictions of virtual narratives of dislocation. This project investigates processes of self-identification, social interaction and physical perception through multimedia works that emerge from digital and textual components. Through interactive and immersive gallery installations, along with participatory workshops, this project questions the notion of a homogeneous self within multiple physical and virtual realms. Dislocation, familiar to those who have experienced cultural migration, has become more apparent as subjects now live as virtual immigrants within the realm of the digital. In cyberspace, subjects and objects exist as images that are constantly moving from one screen to the next, a virtual dislocation similar to the one of a migrant body. The sense of being present and belonging to a specific place is constantly affected by today's digital culture. As augmented digital elements merge with the physical world, a mixed reality emerges in which subjects and objects become re-presentations of themselves. Digital technologies have become an extension of both the body and its consciousness. This allows for the body to experience itself, others and the places around it as multiple and infinite entities. Translational Spaces presents a suspended state of mixed realities in which digital environments are used to trigger a sense of the immediate and the already-lived. This allows the individuals who experience it to construct their own virtual narratives through a sense of (dis)embodiment and dislocation.